Stabilizace břehů nádrží - Martinát, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Cílem tohoto projektu je návrh předsazených vlnolamů na údolní nádrži Brno, oblasti Osada. Tato opatření mají zamezit dalšímu vymílání zeminy na pobřeží, tedy abrazi. Správný návrh spočívá v určení abrazní terminanty AT, tedy bodu, kde se ústup břehu samovolně zastaví. K tomuto bodu je potřeba zpracovat četnosti hladin v nádrži za 10 let, následné stanovení nejčetnější hladiny Mnmax a výpočet výškové úrovně paty nejvýše položeného abrazního srubu Va.

The aim of this project is design front breakwaters on the valley dam Brno, area Osada. These precautionaries must obviate another destruction of soil on coast, abrasion. The correct design is depending on a definition of abrasion terminant AT, it is point where regress of bank stops. We need elaborate counts of water levels in the dam for last ten years, for the definition of that abrasion point. After that follows definition of the most-count water level Mnmax and definition of a ground elevation bottom of the most highly abrasion crib Va.
Bank Stabilization of dam
Keywords: Voda; přehrada; abrazní plošina; četnost výskytu hladin; návrhová výška vlny; opevnění; biotechnická stabilizace; vlnolam; Water; dam; abrasion platform; count of water levels; desing high of water wave; bunding; biotechnical stabilisation; breakwater